Proceedings of the 2005, American Control Conference, 2005.
DOI: 10.1109/acc.2005.1469980
|View full text |Cite
|
Sign up to set email alerts
|

Incipient fault detection in mechanical power transmission systems

Abstract: This paper presents a novel method for anomaly detection in a helical gear box, where the objective is to predict incipient faults before they become catastrophic. The anomaly detection algorithm relies on symbolic time series analysis and is built upon concepts from automata theory, information theory, and pattern recognition. Early detection of slow timescale anomalous behavior is achieved by observing time series data at the fast time-scale of machine operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Several case studies [2][3][4][5] in anomaly detection show that STSA can be more effective than existing pattern recognition techniques (e.g., principal component analysis and neural networks). The STSA method has also been demonstrated for fault detection in electromechanical systems, such as three-phase induction motors [6] and helical gearbox in rotorcraft [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies [2][3][4][5] in anomaly detection show that STSA can be more effective than existing pattern recognition techniques (e.g., principal component analysis and neural networks). The STSA method has also been demonstrated for fault detection in electromechanical systems, such as three-phase induction motors [6] and helical gearbox in rotorcraft [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies [7][8][9] have shown that STSA is more effective at anomaly detection than pattern recognition techniques such as principal component analysis and neural networks. STSA has also been used for fault detection in electromechanical systems, e.g., three-phase induction motors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies [17][18][19] have shown that STSA is more effective at anomaly detection than pattern recognition techniques such as principal component analysis and neural networks. STSA has also been used for fault detection in electromechanical systems, such as in three-phase induction motors [20] and helical gearboxes in rotorcraft [21]. The method that we have developed transforms time series acceleration data into symbolic data series.…”
Section: Introductionmentioning
confidence: 99%